Storytelling as a Communication Tool in Journalism: Main Stages of Development - Markova, Victoriya; Sukhoviy, Olexandr (Journal of History Culture and Art Research, 2020)
In recent years, there has been an increasing interest in storytelling in journalism. The objectives of this study are to highlight the main stages in the development of storytelling as a communication tool in journalism. To achieve the proposed goal the following steps will be taken: The context, in which the term “storytelling” is used, will be determined; scientific publications examining storytelling as a communication tool will be analyzed; specific communicative markers of this tool as distinguished by researchers will be demonstrated; and main stages and patterns of storytelling development as a communication tool will be determined. A study of the developmental history of storytelling as a communication tool in journalism led to the conclusion that it can be divided into two main stages. The first is associated with the development of traditional storytelling in print media, radio, and television. The second is the development of digital storytelling. The principles of storytelling development in journalism are its recognition as a communication tool that can achieve both commercial and social goals, the increase and complication of means to influence the audience with new information technologies, and a paradigm shift from broadcasting to involving. Further studies can be conducted through a quantitative and qualitative analysis of research on storytelling in post-Soviet spaces.